2018
DOI: 10.1097/md.0000000000012007
|View full text |Cite
|
Sign up to set email alerts
|

miR-17–92 cluster is connected with disease progression and oxaliplatin/capecitabine chemotherapy efficacy in advanced gastric cancer patients

Abstract: This study aimed to determine the role of plasma miR-17-92 cluster level in predicting chemoresistance in patients with gastric cancer (GC) undergoing oxaliplatin/capecitabine (XELOX) chemotherapy.Patients recently diagnosed with advanced GC were chosen as participants based on the inclusion criteria. The plasma levels of miR-17-5p, miR-18a, miR-19a/b, miR-20a, and miR-92-1 (miR-17-92 cluster) were determined through quantitative RT-PCR of blood samples from GC patients and healthy volunteers. All the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In addition, a variety of noncoding RNAs are associated with capecitabine and oxaliplatin resistance in GC cells (8,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a variety of noncoding RNAs are associated with capecitabine and oxaliplatin resistance in GC cells (8,15).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization strategies for effective GC CapeOX regimens remain to be found. Studies on genome-wide research have revealed the diversity and the complex genetic alterations of patients with GC, which can explain the differing responses of different patients during chemotherapy (7,8). Currently, few biomarkers for the prediction of CapeOX chemotherapy have been validated for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly increased plasma miR-17-92 cluster levels has been found in advanced gastric cancer patients. Whereas, there was obvious decrease of these miRNAs in chemosensitive individuals after oxaliplatin/capecitabine (XELOX) chemotherapy, indicating they might be used as biomarkers of XELOX treatment [160].…”
Section: Mirnas and Resistance To Other Drugsmentioning
confidence: 99%
“…The miR-17-92 cluster not only participates in the progression of gastric cancer but also could be used to monitor therapeutic utility. Fan et al tested the expression of the miR-17-92 cluster in the plasma of gastric cancer patients undergoing traditional chemotherapy with oxaliplatin/capecitabine (XELOX) [72]. The results showed that the miR-17-92 cluster was expressed at higher levels in advanced gastric cancer and was downregulated after chemotherapy.…”
Section: Su Et Al Examined the Expression Of Mir-18a Using A Taqman mentioning
confidence: 99%